2020
DOI: 10.1177/0018726719894054
|View full text |Cite
|
Sign up to set email alerts
|

Is ‘be yourself’ always the best advice? The moderating effect of team ethical climate and the mediating effects of vigor and demand–ability fit

Abstract: Although we know that individuals who tend to reveal their true selves to others at work are better performers, little is known about why this is the case or in which workplace environments this trait will be most helpful. In the present study, we leveraged selfverification theory to better understand the internal and interpersonal effects that self-verification striving has on employees. Specifically, we proposed and found that self-verification striving serves to increase both employee vigor and demand-abili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(46 citation statements)
references
References 87 publications
3
34
0
1
Order By: Relevance
“…Studies have shown that a team-oriented culture plays a moderating role in providing positive outcomes in organizations (David et al, 2020;Mohammed and Angell, 2004;Patel and Conklin, 2012;Tzabbar and Vestal, 2015;van Knippenberg et al, 2015). For instance, the relationship between perceived organizational support and OCB is strong when the culture is powerfully collectivist (van Knippenberg et al, 2015).…”
Section: Moderating Effect Of Team-oriented Culturementioning
confidence: 99%
“…Studies have shown that a team-oriented culture plays a moderating role in providing positive outcomes in organizations (David et al, 2020;Mohammed and Angell, 2004;Patel and Conklin, 2012;Tzabbar and Vestal, 2015;van Knippenberg et al, 2015). For instance, the relationship between perceived organizational support and OCB is strong when the culture is powerfully collectivist (van Knippenberg et al, 2015).…”
Section: Moderating Effect Of Team-oriented Culturementioning
confidence: 99%
“…The self-verification perspective on group identification Despite the value of self-categorization for group identification, Cable et al (2013) study showed that when the organization focused on personal identity by emphasizing newcomers' authentic self-expression, newcomers provided better customer service and were more likely to stay. In a similar vein, David et al (2021) found that when employees could express their own views, they were more likely to perform well at work. As such, paralleling the selfcategorization pathway, we propose an alternative self-verification pathway.…”
Section: H1 Individual Differentiation Has a Negative Indirect Effect On Group Identificationmentioning
confidence: 83%
“…Finally, our moderated mediation model goes beyond a direct examination of the impacts of verified self-views on work attitudes and behaviors (e.g. David et al, 2021;Swann et al, 2003) by incorporating balance theory to explain when newcomers with high individual differentiation can identify with their group. Previous research utilizing balance theory has focused on the influences of triadic relationships on work outcomes, such as employee job performance (Lan et al, 2020) and coworker interactions (Tse et al, 2013).…”
Section: Jmp 365mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, households with a low-wealth level will pay more attention to economic compensation due to house demolition, since it is an important resource and can more effectively improve the overall quality of life from many aspects. According to the resource conservation theory, when people have more abundant resources, they are less susceptible to the loss of this part of resources and more likely to invest this part of resources to obtain additional resources (Hobfoll, 2011;David et al, 2021). Therefore, households with a low-wealth level will regard economic compensation due to house demolition as valuable resources to a higher extent they will spend relatively less money to avoid psychological pressure and loss caused by resource loss.…”
Section: House Demolition Household Wealth and Family Conspicuous Consumptionmentioning
confidence: 99%